The burden of thalassemia disorder: Past and present: The feedback of patients experience in the COVID-19 pandemic crisis - Anis Arioua; David Shaw (Asian Journal of Transfusion Science)
Thalassemia is a genetic blood condition and one of the emerging global public health concerns in the world, with an estimated prevalence of 300,000,000. The genes controlling hemoglobin production are affected, leading to an anemia of variable severity. Carriers of this hereditary anemia are found globally, but a high frequency is observed around the Mediterranean basin, in the Middle East, in the Indian subcontinent, and in Southeast Asia, so called the thalassemia belt. This article aims to review the history and factors of spreading of thalassemia, to identify the burden of the disease on individuals, population, and public health, and the issues that thalassemia patients have experienced during the pandemic of COVID-19. Online literature and previous studies on the disease are used to prepare this article. We identified various factors that have contributed to the spread of thalassemia in the last decades and affected the health condition of individuals and population. The recent worldwide pandemic of COVID-19 worsened the situation and made it more complicated for most patients, especially in the emerging countries.